Grapevine-Associated Lipid Signalling Is Specifically Activated in an Rpv3 Background in Response to an Aggressive P. viticola Pathovar - Gonçalo Laureano; Catarina Santos; Catarina Gouveia; Ana Rita Matos; Andreia Figueiredo (Cells, 2023)
Vitis vinifera L. is highly susceptible to the biotrophic pathogen Plasmopara viticola. To control the downy mildew disease, several phytochemicals are applied every season. Recent European Union requirements to reduce the use of chemicals in viticulture have made it crucial to use alternative and more sustainable approaches to control this disease. Our previous studies pinpoint the role of fatty acids and lipid signalling in the establishment of an incompatible interaction between grapevine and P. viticola. To further understand the mechanisms behind lipid involvement in an effective defence response we have analysed the expression of several genes related to lipid metabolism in three grapevine genotypes: Chardonnay (susceptible); Regent (tolerant), harbouring an Rpv3-1 resistance loci; and Sauvignac (resistant) that harbours a pyramid of Rpv12 and Rpv3-1 resistance loci. A highly aggressive P. viticola isolate was used (NW-10/16). Moreover, we have characterised the grapevine phospholipases C and D gene families and monitored fatty acid modulation during infection. Our results indicate that both susceptible and resistant grapevine hosts did not present wide fatty acid or gene expression modulation. The modulation of genes associated with lipid signalling and fatty acids seems to be specific to Regent, which raises the hypothesis of being specifically linked to the Rpv3 loci. In Sauvignac, the Rpv12 may be dominant concerning the defence response, and, thus, this genotype may present the activation of other pathways rather than lipid signalling.